What happened to the genus Gammarus (Crustacea: Amphipoda) in Central Asia - Boris Sket; Dmitry Sidorov; Zhonge Hou (Acta Biologica Slovenica, 2019)
We examined the phylogenetic relationships in the unusually structured fauna of the amphipod genus Gammarus in Central Asia, trying to explain its causes. Mitochondrial DNA sequence data were used in MP and ML and Bayesian analyses to generate a phylogenetic hypothesis. All of the recently collected Gammarus spp. specimens belong to the G. lacustris aggregate, except scarce marginal populations of G. balcanicus and G. komareki aggregates. Although molecularly closely related, these. G. lacustris agg. populations are morphologically and ecologically equally diverse as are the numerous European Gammarus spp. Only few populations are morphologically close to the morphotype of G. lacustris. There is a more than 2,000 km wide gap between the eastern and western populations-species of G. balcanicus agg. Since Gammarus lacustris can be spread by birds, and its Asian relatives are molecularly significantly diverse, we suppose that it invaded Central Asia several times and from several sources. It most probably differentiated to diverse morphotypes after reaching Asia. The area of the cryophilic and less nomadic G. balcanicus could have been reached and conquered only by waterways. Its area was probably continuous in the past and divided by aridification during the Neogene. The strong historical aridifications probably extirpated the probably higher Gammarus diversity in Central Asia, including G. balcanicus. This opened the area and its habitats for the reiterated invasions of the particularly euryoecious G. lacustris s.l., followed by its morphological and ecological diversification.